INTUSSUSCEPTION IN INFANTS AND CHILDREN-AN ANALYSIS OF 130 CASES IN ABBOTTABAD AND HAZARA DIVISION - Gandapur, Abdus Salam Khan; Muhammad, Gal; Awan, Faisal Nazir; Tayyab, Muhammad (Journal of Ayub Medical College Abbottabad, 2000)
Background: Intussusception is the commonest cause of intestinal obstruction in children. We reviewed 130 cases over a period of 10 years at DHQ hospital. Abbottabad to assess their mode of presentation, methods of investigation, management and outcome. Methods: A retrospective review was performed of the case notes of presentation, investigation, management and subsequent outcome. Results: Although majority of patients presented with the classical triad of abdominal pain 88%, vomiting 82% and rectal bleeding 54%. There were some who varied in their mode of presentation. A presumptive initial diagnosis of infective diarrhoea or colitis and referral for a medical rather than surgical opinion was made in 86(69%) cases. Hydrostatic reduction was done in 79% of cases, 29 being successful. Laparotomy was done in 101 cases. In 6 patients (6%) spontaneous reduction occurred between barium enema reduction and subsequent laparotomy. Simple manual reduction after laparotomy was done in 45 cases. Resection of the gangrenous intestine was done in 13 patients. In the rest of 37 patients, various operations like right hemicolectomy and appendectomy were done. Conclusion: The male to female ratio in our series was almost equal. No variation in the relationship between incidence and season or type of feeding was found. Ileocolic intussusception was found to be the commonest type at the laparotomy in our series.